Labour Migrants Experience and Change in Aspiration - SHRESTHA HYSOP (Graduate School of International Studies Ajou University, 2020)
Migration is well-known traditional phenomenon and has experienced an increasing rate globally. There are diverse purposes for migration, such as to search for a job opportunity, for security, trade, to obtain a higher education and many others. This research paper clearly highlights migration and its implication for the future career aspirations of Nepalese migrant workers. Several factors impede migrant workers' change in aspirations, such as their experience. Furthermore, research in this paper is focused on several changes of return migrants and their perception, behavior, knowledge, skill and other aspects based on their experience. The different demographic factors were analyzed based on their ages, ethnicity, gender, religion, geographic location, etc. Socioeconomic factors have been studied as one of the major factors that affect migration. The factors that lead people to migrate, either voluntarily or involuntarily, permanently or temporarily, are commonly referred to as the ‘drivers’ of migration. Evidence-based drivers of migration can be economic, demographic, environmental, social, and/or political. This paper applied 162 samples from return migrant workers under the EPS system from different areas of Nepal. The respondents completed 47 questions measuring different parameters that affected migration experience and change in aspirations. Questionnaires were open and closed end types with various measurement scales. This study used descriptive statistics to measure the characteristics of the participants. Several analyses were used statically by presenting on tables with percentile and frequencies. SPSS was the major tool used for data analyses. According to the findings, return migrants’ socioeconomic status seems to show a positive change after migration. Changes were found in aspirations in the pre and post-migration period of the returnees and that, according to the respondents’ answers, there was a significant role of location and colleagues in changing the aspiration of the migrants. There were enormous changes of returnees in their behavior, perception, knowledge and skills after migration.
학위논문(석사)--Graduate School of International Studies Ajou University :국제개발협력과,2020. 8
Keywords: Aspiration; Labor Migrants; Migration; Return Migrants